Dilated Cardiomyopathy: A New Era of Treatment - Correia, Vinícius Machado; Oliveira, Lucas Lentini Herling de; Junior, Vagner Madrini; Rocha, Ruiza Gonçalves; Leguizamon, Juliana Alzira Gonzales O; Costa, Leandro Menezes Alves da; Fernandes, Fabio; Krieger, Jose Eduardo; Soares, Paulo Rogério; Scudeler, Thiago Luis (Cardiology and Cardiovascular Medicine, 2024)
Dilated cardiomyopathy (DCM) is a common form of cardiomyopathy, characterized by ventricular chamber dilatation and systolic dysfunction, in the absence of coronary artery disease, arterial hypertension, valvular or congenital diseases. DCM is a heterogeneous group of disorders of the myocardium caused by genetic factors, environmental factors, or a combination of both. DCM affects mainly men aged between 20 and 50 years, being considered one of the main causes of heart failure (HF) and the main indication for heart transplantation. Guideline-based HF treatment is the mainstay of management for patients with DCM. In recent years, gene therapy and induced pluripotent stem cells have become promising strategies. In this review, we summarize the relevant clinical issues, and current treatment of DCM patients, including the role of genetic evaluation.